Religious Faith as a Factor of the Modern Youth’s Psychic and Psychological Health - Savelyuk, N. M. (Psychological Prospects Journal, 2012)
The article gives the theoretical analysis of psychic and psychological health, and its main components and factors. Among all other factors of the personality’s functioning sphere the very special attention is given to the phenomenon of religious belief with its mighty spiritual potential. The preconditions of transforming religiosity into the category threatening the safety of the emotional human’s well-being are revealed as well. On the example of the results of the content-analysis of the students’ thematic works the author proves the important role of Christian faith in supporting the modern youth’s psychic and psychological health.